Implementation of a mobile robot to optimize the documentation flow in the logistics area using autonomous robotics technologies based on the free software platform ROS - Calle Flores, Iván (2017)
The present project is about the implementation of an autonomous mobile robot designed for logistic tasks in different areas of a company, university, etc. This robot is able to navigate autonomously in real environments, you just need to specify the initial position, the grip map of the world and the target locations, and the robot will generate automatically the optimal path to reach the target positions, and then will follow this path while avoiding obstacles such as persons, trash bins, etc. These characteristics allow that our robot can be used in logistic tasks where the robot needs to carry loads from one place to another. In this project we developed two robot models, the first one called R2d2‐R1 can carry loads of up to 3kg, and the second one called can carry loads of up to 25Kg. The algorithms implemented in this project represent the state‐of‐the‐car methods and its performance has been proved in the several experiments carried out with these two robots.